2023
DOI: 10.1007/s00167-023-07516-7
|View full text |Cite
|
Sign up to set email alerts
|

Delaying ACL reconstruction is associated with increased rates of medial meniscal tear

Abstract: Purpose The aim of this study was to evaluate the relationship between the time from injury to ACL reconstruction (ACLR) and the rate as well as repairability of meniscal tears. Secondary aims were to evaluate the relationship between meniscal injury and Tegner Activity Scale, age, BMI, and gender. Methods Between 2012 and 2022, 1,840 consecutive ACLRs were performed. A total of 1,317 ACLRs were included with a mean patient age of 31.2 years ± 10.5 . Meniscal tear was assessed during arthroscopy using the ISAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Furthermore, it has been suggested that restoring anterior/posterior and rotational knee laxity could help prevent further instability and subsequent damage to the articular cartilage and meniscus. For example, delayed ACL reconstruction for 5 months doubled the risk of medial meniscal surgery after ACL injury, and if delayed for 1 year, the risk was six times higher [7,40]. Therefore, using our model to predict a specific tear type could enable tear growth tracking to prevent severe injuries to adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that restoring anterior/posterior and rotational knee laxity could help prevent further instability and subsequent damage to the articular cartilage and meniscus. For example, delayed ACL reconstruction for 5 months doubled the risk of medial meniscal surgery after ACL injury, and if delayed for 1 year, the risk was six times higher [7,40]. Therefore, using our model to predict a specific tear type could enable tear growth tracking to prevent severe injuries to adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…MM serves as a secondary stabiliser and exerts a significant posterior wedge effect. Consequently, in cases of ACL deficiency, the stress on the MM intensifies [23,25,26]. Furthermore, excessive anterior tibial translation resulting from ACL degeneration can increase the strain on the posterior segment of the MM, contributing to the development of MMPRTs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Other possible reasons for the higher risk of contralateral injuries include biomechanical changes or altered neuromuscular function after ACL reconstruction [7], and concomitant MM injury or MM repair may also affect these factors. Therefore, it is recommended that ACL reconstruction be performed early after ACL injury to reduce concomitant MM injury [5,12]. The condition of the ACL reconstructed knee may have influenced contralateral ACL injury.…”
Section: Discussionmentioning
confidence: 99%